2020
DOI: 10.1039/d0cp01160f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and spin exchange coupling in strained monolayer CrOCl

Abstract: The magnetism and spin exchange coupling of monolayer CrOCl with different strains are investigated systematically using first principles. It is found that the magnetic ground state can be changed from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…Additionally, the magnetic properties of few-layer samples are also unknown. These issues have been receiving increasing interest recently and have been studied through theoretical calculations. However, due to the complexity of the three filled 3d orbitals, some calculation results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the magnetic properties of few-layer samples are also unknown. These issues have been receiving increasing interest recently and have been studied through theoretical calculations. However, due to the complexity of the three filled 3d orbitals, some calculation results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2017, long-range 2D FM ordering was experimentally observed in the CrI 3 monolayer (Curie temperature, T c , of ∼45 K) and Cr 2 Ge 2 Te 6 atomic layers ( T c of ∼25 K) , due to the breaking down of the electronic isotropy in these materials. This brings great encouragement to this research field because 2D FM materials are essential for next-generation spintronic devices. , Although CrX 3 (X = F, Cl, Br, I), CrXTe 3 (X = Si, Ge) monolayers, Janus Cr 2 Cl 3 I 3 , and 2H-VSeTe monolayer and CrOCl have been theoretically predicted to be intrinsic FM semiconductors (FMSs), only a few intrinsic 2D FMSs have been reported in laboratory until now . Thus, finding and synthesizing other novel 2D FM crystals with high T c is still a serious issue for practical electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…This brings great encouragement to this research field because 2D FM materials are essential for next-generation spintronic devices. 17,18 Although CrX 3 (X = F, Cl, Br, I), 19−22 CrXTe 3 (X = Si, Ge) 23 monolayers, Janus Cr 2 Cl 3 I 3 , 24 and 2H-VSeTe 25 monolayer and CrOCl 26 have been theoretically predicted to be intrinsic FM semiconductors (FMSs), only a few intrinsic 2D FMSs have been reported in laboratory until now. 27 Thus, finding and synthesizing other novel 2D FM crystals with high T c is still a serious issue for practical electronic applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Aside from the strong interest in the fundamental physics of MOCl compounds, a renewed interest in the application of FeOCl-type compounds resulted in reports about the use as catalysts [14][15][16][17], nonlinear optical materials [18], and developments in the context of chloride ion batteries [19][20][21][22][23]. Research on this specific class of compounds was further boosted by the proposal of MOCl as van der Waals heterostructures [24], and their use as two-dimensional (2D) intrinsically magnetic monolayer materials, e.g., for applications in the field of spintronics [25][26][27][28][29][30][31]. Zhang et al [32] reported liquid exfoliation of FeOCl into few-layer thick nanosheets, a feature that was explained by the low cleavage energy of 340 mJ m −2 being close to the value of 320 mJ m −2 for graphite.…”
Section: Introductionmentioning
confidence: 99%